Deaf Cognition 2008
DOI: 10.1093/acprof:oso/9780195368673.003.0003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Effectiveness of Cochlear Implants in Deaf Children

Abstract: Abstract.A large body of clinical research over the last decade demonstrates that cochlear implants work and provide significant speech and language benefits to profoundly deaf adults and prelingually deaf children. The most challenging research problem today is that cochlear implants do not work equally well for everyone who has a profound hearing loss and cochlear implants frequently do not provide much benefit at all under highly degraded listening conditions. Some individuals do extremely well on tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 139 publications
(137 citation statements)
references
References 92 publications
5
128
0
4
Order By: Relevance
“…As noted earlier, this finding has been suggested to reflect greater difficulty and differing goals of reading at the high school level (Archbold, 2015), the need for longer term interventions following cochlear implantation (Nittrouer & Caldwell-Tarr, 2016) or the involvement of alternative cognitive and environmental factors. Additional possibilities include long-term effects of hearing deprivation prior to cochlear implantation or the cumulative impact of early experiences of hearing loss that are not fully remediated by cochlear implantation, such as delays in EF (Kronenberger, Beer et al, 2014), underspecified cognitive representations of language, or limitations in some settings such as hearing in noise (Pisoni et al, 2008). In any case, similar evidence is emerging with regard to the social-emotional domain, as several other studies have failed to find differences between CI users and nonusers among older children and youth on dimensions such as the frequency of behavior problems, self-acceptance, and social participation (e.g., Hintermair, 2013;Leigh et al, 2009;Schick et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, this finding has been suggested to reflect greater difficulty and differing goals of reading at the high school level (Archbold, 2015), the need for longer term interventions following cochlear implantation (Nittrouer & Caldwell-Tarr, 2016) or the involvement of alternative cognitive and environmental factors. Additional possibilities include long-term effects of hearing deprivation prior to cochlear implantation or the cumulative impact of early experiences of hearing loss that are not fully remediated by cochlear implantation, such as delays in EF (Kronenberger, Beer et al, 2014), underspecified cognitive representations of language, or limitations in some settings such as hearing in noise (Pisoni et al, 2008). In any case, similar evidence is emerging with regard to the social-emotional domain, as several other studies have failed to find differences between CI users and nonusers among older children and youth on dimensions such as the frequency of behavior problems, self-acceptance, and social participation (e.g., Hintermair, 2013;Leigh et al, 2009;Schick et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Pisoni et al (2008) assert that significant cortical reorganization has likely already taken place in the brains of young children with hearing loss prior to cochlear implantation because of sensory deprivation. They contend that neural reorganization, particularly in the frontal cortex, affects aspects of speech and language development, other cognitive processes, such as executive function and cognitive control processes, and neural systems.…”
Section: The Problemmentioning
confidence: 99%
“…Previous research has demonstrated that early identification of hearing loss and subsequent intervention methods and choices have a significant impact on infants' linguistic and cognitive development (Bergeson et al, 2003(Bergeson et al, , 2005Houston et al, 2003;Moeller, 2000;Pisoni et al, 2008;Yoshinaga-Itano et al, 1998). Research with normal-hearing infants suggests that both the quality (Kaplan et al, 2002;Kaplan et al, 1999;Liu et al, 2003) and quantity (Hart and Risley, 1995;Hurtado et al, 2008) of infant-directed (ID) speech is directly related to infants' language, cognitive, and socio-emotional development.…”
Section: Introductionmentioning
confidence: 99%